Res opportunae nostrae aetatis: studies on the Second Vatican Council offered to Mathijs Lamberigts - Bosschaert, Dries; Leemans, Johan; Lamberigts, Mathijs (Ephemerides theologicae Lovanienses, 2020)
The Second Vatican Council is one of the central themes in the research of Mathijs Lamberigts. He contributed to the study of the redaction history of many Council documents and highlighted the role of individual participants at the Council. As director of the Centre for the Study of the Second Vatican Council, he took great care in preserving and making accessible the archives of conciliar participants, especially those of the 'squadra belga'. As a scholar and supervisor, he promoted the spirit and the letter of the Council as an ongoing commitment to many.0The twenty-three contributions in this volume all bear witness to the same commitment to study the history and texts of the Council. 0With these contributions Mathijs Lamberigts' former students and colleagues wish to honour and continue his research on the Second Vatican Council